Komunikasi Intrapersonal Yang Digambarkan Tokoh The Boy dalam Novel The Witches Karya Roald Dahl - Ihsan Surya Pratama (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
The title of this research is intrapersonal communication represented by the character The Boy in the novel The Witches by Roald Dahl. In this novel, it tells the story of an eight years old child without a full name who is refererred to as The Boy as the only child in a family. When both of his parents died in an accident, The Boy lived with his Grandmother who is Norwegian. His Grandmother told The Boy many things that many people from other countries would not easily believe about the existence of a witch who often killed young children so that he also experienced intrapersonal communication to understand his situation as a child and doubted the truth of the words spoken by his Grandmother. The purpose of this research is to describe how intrapersonal communication is experienced by the character by using character theory based on Abrams and intrapersonal communication theory based on Suryanto, Bahfiarti, and Mukarom. This research method uses a qualitative descriptive method based on the theory of Bogdan and Taylor. The objective approach is the approach used in this study based on Ratna’s theory to describe the intrapersonal communication of The Boy.